2015
DOI: 10.1038/bjc.2015.169
|View full text |Cite
|
Sign up to set email alerts
|

PTEN loss is associated with follicular variant of Middle Eastern papillary thyroid carcinoma

Abstract: Background:PTEN gene at chromosomes 10q23.3 is a tumour suppressor gene that is inactivated in many types of human cancers. The known mechanisms of PTEN inactivation are rendered to mutation, epigenetic silencing by aberrant methylation or gene deletion. Although PTEN role has been documented in many cancers, PTEN alteration in papillary thyroid carcinoma (PTC) has not been fully elucidated. The aim of this study is to comprehensively investigate PTEN alterations in a large cohort of Middle Eastern papillary t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…The probe CEN5q was utilized as reference probe for enumeration. FISH on a TMA was performed as previously described . Tissue samples were classified with a TERT and CEN5q ratio of 1.0 as normal; between 1.0 and 2.0 as having TERT gains; and 2 or over 2 as amplified.…”
Section: Methodsmentioning
confidence: 99%
“…The probe CEN5q was utilized as reference probe for enumeration. FISH on a TMA was performed as previously described . Tissue samples were classified with a TERT and CEN5q ratio of 1.0 as normal; between 1.0 and 2.0 as having TERT gains; and 2 or over 2 as amplified.…”
Section: Methodsmentioning
confidence: 99%
“…Accruing works have revealed that PTEN is involved in progression of cancers and negatively correlated with AKT signaling in hypopharyngeal carcinoma, non-small cell lung cancer and esophageal squamous cell carcinoma [13][14][15]. Previous study suggested that loss of PTEN is associated with progression of papillary thyroid cancer [16]. In this study, we sought to investigate the roles of miR-17-5p and PTEN in thyroid cancer progression and explore the potential interaction between miR-17-5p and PTEN/AKT/mechanistic target of rapamycin (mTOR) signaling pathway.…”
mentioning
confidence: 99%
“…However, PTEN is a well-known tumor suppressor gene, and loss of PTEN expression isassociated with aggressive behavior and poor prognosis in cancer [ 19 ]. PTEN-deleted mice easily developed malignant tumors [ 20 ]. FOXO1/3 and PTEN depletion in granulosa cells also promoted ovarian granulosa cell tumor development [ 21 ].…”
Section: Discussionmentioning
confidence: 99%